THE ROLE OF ENTREPRENEURSHIP IN REDUCING POVERTY THROUGH ISLAM PERSPECTIVE - Vebby Anwar; Sofyan Hamid (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2019)
Entrepreneur is a stratetegical economic change agent for the Indonesian people in reducing poverty. By seeing that the majority of Indonesia's population is Muslim so it is very appropriate to implement an Islamic-based entrepreneurship system. Entrepreneur is a system in accordance with the teachings of Islam because it is highly recommended to seek riski or income. Islamic teachings view that work is a worship, so that entrepreneurs besides can lift income per capita, also can reduce poverty. In this library research emphasize the importance of entrepreneur applied in Islam because in view of Islam is aspect of life which is grouped into muamalah problem which closely related to relation between human with God which will be accounted later in akhirat. Business in the Qur'an is a human trade with God associated with spending his rescue to someone who can not afford. Successful behavior in Islam can not simply come, there are many values that need to be interpreted by Muslims as an entrepreneur. One of them, the orientation that becomes a good conception of self or others who become habit as way of life (way of life). Analysis of the success of an Islamic entrepreneur is to consider the variables of success and failure with internal and external factors based on Islamic teachings.